2020
DOI: 10.1088/1748-0221/15/11/p11014
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of germanium detectors for the first underground laboratory in Mexico

Abstract: This article reports the characterization of two High Purity Germanium detectors performed by extracting and comparing their efficiencies using experimental data and Monte Carlo simulations. The efficiencies were calculated for pointlike γ-ray sources as well as for extended calibration sources. Characteristics of the detectors such as energy linearity, energy resolution and full energy peak efficiencies are reported from measurements performed on surface laboratories. The detectors will be deployed in a γ-ray… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…(meter water equivalent) overburden. LABChico is focused on the development of research and educational programs through the establishment of a γ-ray assay facility initially consisting of two High Purity Germanium detectors [27]. A dedicated program in fundamental and applied science is devised, where γ-ray assay of detector components for underground astroparticle physics will be developed, in addition to environmental radiation monitoring applications, see [2,3,4,5,6,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…(meter water equivalent) overburden. LABChico is focused on the development of research and educational programs through the establishment of a γ-ray assay facility initially consisting of two High Purity Germanium detectors [27]. A dedicated program in fundamental and applied science is devised, where γ-ray assay of detector components for underground astroparticle physics will be developed, in addition to environmental radiation monitoring applications, see [2,3,4,5,6,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The results in sections V-A and V-B below were obtained with spectra from a set of radioactive sealed calibration sources (Table III) and they were acquired with an EG&G-ORTEC Hyper Pure Germanium detector in the Detectors Laboratory at the Institute of Nuclear Science of the National Autonomous University of Mexico (UNAM), hereafter referred to as ICN-HPGe detector, whose characterization has been reported elsewhere [44]. The data acquisition system (DAQ) was a PX5-HPGe multi-channel analyzer (MCA) and a digital pulse processor (DPP) software analyzer provided by Amptek [45].…”
Section: Methodsmentioning
confidence: 99%
“…Nonetheless, no significant improvements were observed when efficiency corrected spectra were used as input. Therefore, identification could be achieved without knowing the detector's efficiency [44]. Besides, a test was implemented to find the dependence of the ranking results against the peakto-background ratio (PBR) defined as the ratio of the area enclosed by a peak to the area of the background beneath it, in an interval ±3σ around the peak, and calculated using an exponential plus second order polynomial fit.…”
Section: B Comparison Of Criteria Using Known γ-Sourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the assay conducted at Boulby using the RosebeRRy BEGe detector, the 210 Pb water samples were also characterised at the Institute of Physics of the National Autonomous University of Mexico (IF UNAM) using the BEGe detector described in Aguilar-Arevalo et al (2020a). The measurements and calibration with both IF UNAM and Boulby Germanium detectors were consistent as described in Aguilar-Arevalo et al (2020a) and shown in Table 4. For the Boulby measurements, the statistical and systematic effects described for Table 3 also apply here.…”
Section: Hpge Analysismentioning
confidence: 99%